(3GdMH Hjf GHf MRe hGHf GdaGQV (B= s Love according to Ebn Hazm and Ebn Elfared - (3MhQjI NdjaI ejdhO GdWQeGd s; (3UdGM GdOjf HSjhfi QSdGf (B: s ((3GdbGgQI (B: s (3MhQjI NdjaI ejdhO GdWQeGd (B: s, 2012)
(3LGAJ QSGdJi HYfhGfgG GdMH Hjf GHf MRe hGHf GdaGQV heG gi EdG ESgGe eJhGVY ef CLd hVY dHfg hdh UZjQg ai SHjd EKQGA GdecJHI GdESdGejI HgPG GdLGfH GdeejR ef GdYdGbI Hjf GdEfSGf hGdCNQ hHjf GdEfSGf hGddg SHMGfg hJYGdi Ef GdhGba Ydi MbjbI GdESdGe hCUhdg GdWjHI jOQc HYbdg GdfjQ hacQg GdeSJbje Cf GdOjf GdESdGei GdMfja djS eLQO TYGFQ eNUhUI ai CeGcf GdYHGOI hcai Hd gh Ojf Sdhc heYGedGJ hGfaYGdGJ hYhGWa heTGYQ aGdMH ai GdESdGe efgL dg MOhO hWQjb heYGde hbjhOs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GdadSaIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdEfSGf s; (3GdJUha s; (3GdMH s